Peran E-commerce Terhadap Penjualan Usaha pada Industri Pakaian jadi di Provinsi Bali - Setyawan, I Gusti Ngurah Adi; Sukadana, I Wayan; Saientisna, Made Detriasmita (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2017)
This Study is aimed to know how much the influence of e-commerce to sales and to know which type of e-commerce has the most influence on sales. This study was conducted at apparel industry in Bali Province. The sample in this study is 100 business units at apparel industry in Bali Province. The analysis technique used in this study is instrumental variabel (IV). The results of this study indicate that the value of sales by using e-commerce is 258 percent greater than the value of sales without using e-commerce. The value of sales using Facebook is 46 percent greater than using other types of e-commerce. It is also known that the sales of t-shirt clothing is bigger 1.3 percent instead of other kind of clothing. This study also shows overseas or exported marketing has 82 percent greater sales than local or domestic marketed.   Keywords : e-commerce, apparel industry, sales, instrumental variables